Landscape and coloniality are robust predictors of White Stork nest habitat selection in a coastal urban environment. (5th September 2020) - Hmamouchi, Mohamed-Jad; Agharroud, Kamal; Dahmani, Jamila; Hanane, Saâd
Abstract: Understanding factors influencing the nest site selection of birds in coastal cities is a major topic in urban ecology, with important management and conservation implications. We investigated the White Stork (WS, Ciconia ciconia ) nest habitat use in the coastal city of Rabat, Morocco. We used data on a series of topographic, landscape, coloniality and spatial parameters to identify the best predictors of nest presence using generalized linear models. These variables were measured at nest supports (n = 107) and supports with no nests (n = 107) within 1.5 km radius landscape. The results showed a high probability of WS nest presence on a 4° slope, an exposition between 148 and 172 °N, elevation above 130 m, near roads, approximately 2300 m from the nearest river, from 5 to 28% agricultural areas, and a cover of villas with tall-trees higher than 60%. WS nest presence occurs also in buffers with more than 20 nests and those with less than 500 m between nest supports. Variation partitioning analysis revealed that the joint effect of landscape and coloniality (17%) and landscape, coloniality and space (17%) are important for nest site selection by WS. In Rabat, WS nests are mainly established in the villa zone with trees and also in the already occupied areas. These results will have important implications for the Rabat urban environmental managers in managing this coastal city while considering the needs of breeding storks. Highlights: Factors affecting the White Stork nest presence are yet not assessed in coastal urban Morocco. Landscape and coloniality significantly influence White stork nesting habitat in Rabat. White Stork nests are mainly established in the villa zone with trees and in already occupied areas. Results are relevant to managing the breeding storks in the coastal city of Rabat.